Temperature Sensor by Using Selectively Filled Photonic Crystal Fiber Sagnac Interferometer - Ying Cui (IEEE Photonics Journal, 2012)
In this paper, we report an optical fiber Sagnac interferometer (OFSI)-based temperature sensor constructed by a selectively filled polarization-maintaining photonic crystal fiber (PM-PCF). The transmission spectrum of the OFSI is in sinusoidal form and is sensitive to temperature. Simulation results predicted a higher sensitivity by selective filling than nonselective filling. In experiments, we used an extremely low-cost process to realize the selective filling. A sensitivity of 2.58 <tex Notation="TeX">$\hbox{nm}/^{°}\hbox{C}$</tex> was achieved with an 11.7-cm-long PM-PCF. The sensitivity dependence on the infiltration length ratio was also investigated.